ISLAMIC EDUCATION IN THE CONTEXT OF INDONESIA NATIONAL EDUCATION - Muchtarom Muchtarom (Jurnal Pendidikan Islam, 2013)
Islamic Religion Education has been part of National Education System, however, its existence and contribution are less significant especially in empowering the nation. In fact, Islamic education has great potential in building character. This paper aims at identifiying and analyzing the efforts on Islamic Religion Education development in National Education System. This study used descriptive analysis method through literature review as secondary data. The result shows that Islamic Religion Education development in National Education System attempted to eliminate dycothom between general education and religion education independently. Otherwise, it must have a collaboration with other education. In sum, Islamic Religion Education is not only legitimized in a whole as a part of National Education System but also it requires a curriculum change that collaborate Islamic Religion Education System with other subjects.